Centromere and its associated proteins—what we know about them in Plasmodium falciparum. Issue 8 (22nd June 2018) - Verma, Garima; Surolia, Namita
Abstract: The complex life cycle of intracellular parasitic protozoans entails multiple rounds of DNA replication and mitosis followed by cytokinesis to release daughter parasites. To gain insights into mitotic events it is imperative to identify the biomarkers that constitute the chromosome segregation machinery in the parasite. Chromosomal loci called centromeres and their associated proteins play an essential role in accurate chromosome segregation. Although new information on the centromere‐kinetochore proteins has been added to the existing pool of knowledge, a paucity of biomarkers for nuclear division prevents a global view of chromosome segregation mechanism in the malaria parasite. In Plasmodium falciparum, except CENH3 and CENP‐C homologues, other centromere associated proteins responsible for centromere functions and kinetochore assembly are not known. The focus of this review is to summarize the current understanding on the centromere organization and its associated proteins in eukaryotes with the emerging information in P. falciparum . © 2018 IUBMB Life, 70(8):732–742, 2018